Shorter telomere length in children with autism spectrum disorder is associated with oxidative stress - Zhang, Tong; Sun, Yanan; Wei, Jing; Zhao, Guoqiang; Hao, Wenqi; Lv, Zhihai; Chen, Xiaohang; Liu, Yanan; Wei, Fengxiang (Frontiers in Psychiatry, 2023)
Objective: Autism spectrum disorder (ASD) is a highly heterogeneous neurodevelopmental disorder caused by a complex interaction between genetic and environmental risk factors. The balance between antioxidant capacity and oxidative stress (OS) induced free radicals may be crucial during the pathophysiological development of ASD. Methods: In this study, 96 children with ASD who met the diagnostic and statistical manual of mental disorders were collected, and the number of children in the typical development (TD) group was matched by 1:1. Digital PCR (dPCR) for telomere length (TL) expression in ASD in peripheral blood leukocytes. Urine levels of 8-hydroxy-2-deoxyguanosine (8-OHdG) content were measured by tandem triple quadrupole mass spectrometry and corrected by urinary creatinine levels. The levels of superoxide dismutase (SOD), catalase (CAT), and capacity (AOC) were detected by kits. Results: The TL of the ASD group was shorter than the TD group (P < 0.01) and had some accurate predictive significance for the identification of ASD (AUC = 0.632, 95% CI: 0.533-0.710, P = 0.002). Both 8-OHdG content and SOD activity in the ASD group were significantly higher than those in the TD group (P < 0.05). Shortened TL (Multifactor: 2.22(1.22, 4.00), P = 0.008) and reduced CAT activity (Multifactor: 2.31(1.28, 4.18), P = 0.006) are risk factors for the development of ASD, while reduced 8-OHdG content (Multifactor: 0.27(0.13, 0.57), P = 0.001) and reduced SOD activity (Multifactor: 0.54(0.30, 0.98), P = 0.042) are protective factors for the development of ASD. Conclusion: In this study, TL and OS were significantly different between the ASD group and the TD group. As guanine-rich telomere sequences were likely damaged by oxygen free radicals, creating OS, which is a factor in the incidence and progression of ASDs. In conclusion, oxidative damage occurs in the bodies of children with ASD, which may lead to sustained disease progression and severe clinical manifestations. We assume that timely supplementation of antioxidants is very likely to be a potential treatment for early intervention in children with ASD. Identification and detection of OS-related biomarkers may contribute to early diagnosis and timely interventions in young patients with ASD.